Hate Music - Claude Chastagner (Transatlantica)
On August 5, 2012, Wade Michael Page killed six Sikhs outside their temple in Wisconsin. Page was an avowed white supremacist and belonged to several bands playing openly racist music and connected to neo-Nazi organizations. This article explores the connection between “hate music” and racist organizations, and wonders about the potential power of music to generate violence.